Designing a Research-Oriented Curriculum in Islamic Secondary Education: An Analysis of Curriculum Development Components in Madrasah - Hawwin Muzakki; Moh. Arif; Manavavee Mamah; Muh. Ibnu Sholeh (Edudeena : Journal of Islamic Religious Education, 2026)
This research discusses the establishment and implementation of a research curriculum in Islamic secondary education utilizing MAN 2 Tulungagung as a research-oriented madrasah model. The study investigates four major questions: (1) how the curriculum objectives integrate scientific inquiry and Islamic values; (2) how the content of research is organized and presented; (3) how instructional methods support the development of research skills; and (4) how research learning outcomes are evaluated and enhanced by evaluation mechanisms. Data were collected through a qualitative case study comprising in-depth interviews with school administrators, research mentors, and curriculum coordinators; document analysis; classroom observations; and focus group discussions. The data were assessed using a curriculum development framework based on Tyler’s model, focusing on the consistency of objectives, learning experiences, content organization, and evaluation. The findings show that the research curriculum is intended as an integral and value-based structure. Curriculum objectives combine scientific rigor and Islamic ethical formation; content provides a balance between theoretical research knowledge and applied inquiry; instructional techniques are student-centered and inquiry-based; evaluation includes thorough formative and summative assessments. This integrative methodology promotes students’ research literacy, critical thinking, and moral responsibility. Theoretically, this study demonstrates how Islamic secondary education can create a space for research-based learning in a faith-based framework. In practice, this study provides a curriculum model that madrasahs can replicate to strengthen research culture and global academic competitiveness while maintaining religious identity. The concept also represents an innovation in curriculum administration, particularly in integrating research mentoring, student differentiation, and institutional evaluation mechanisms.